2018
DOI: 10.12968/jowc.2018.27.7.426
|View full text |Cite
|
Sign up to set email alerts
|

Topical oxygen therapy stimulates healing in difficult, chronic wounds: a tertiary centre experience

Abstract: Use of TOT in chronic wounds stimulates a healing state. In our study, almost half of the previously non-healing wounds closed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 22 publications
0
24
0
1
Order By: Relevance
“…Considering the benefits that slow oxygen release seems to induce in wound healing [12] [13] and its beneficial effects in the few clinical studies related to periodontal diseases, more studies are needed to investigate the effect of this new gel on periodontitis and on Porphyromonas gingivalis.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the benefits that slow oxygen release seems to induce in wound healing [12] [13] and its beneficial effects in the few clinical studies related to periodontal diseases, more studies are needed to investigate the effect of this new gel on periodontitis and on Porphyromonas gingivalis.…”
Section: Introductionmentioning
confidence: 99%
“…An initial pilot study on 10 chronic DFU wounds has shown promise; a median healing rate of 53% was achieved after eight-week long treatment with Natrox (Hayes et al, 2017). Similar results were achieved with a larger cohort of varying types of chronic wounds, including DFUs, venous leg ulcers, and arterial leg ulcers (Kaufman et al , 2018). The aim of this randomised, controlled, prospective clinical trial is to determine if the device is acceptable and feasible to introduce into foot ulcer treatment.…”
Section: Introductionmentioning
confidence: 84%
“…As a secondary objective, the efficacy of the Natrox topical oxygen therapy device as an adjunct therapy for foot ulcers will be assessed. The rationale behind including both diabetic and non-diabetic foot wounds is that the mechanism of action of Natrox is not affected by a patient's diabetes status and the product has shown promise in non-diabetic wounds (Kaufman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although both may possess anti-infective properties, infection and necrosis should be regulated with surgery and antibiotics. The clinical outcomes of NPT are widely presented in the literature [ 32 ]; however, salvage of the so-called “peripheral gray area” has been difficult to achieve with NPT. HBOT has also recently been approved to treat patients with chronic, non-healing or complicated wounds [ 33 ].…”
Section: Discussionmentioning
confidence: 99%